2017
DOI: 10.3168/jds.2017-12889
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Repeated mammary tissue collections during lactation do not alter subsequent milk yield or composition

Abstract: Mammary biopsy collection (MB) is a valuable approach for studying mammary gland biology, but it is unclear if repeated MB impair the performance of lactating dairy cows. The objective of this trial was to examine the effect of repeated MB during lactation on udder health, dry matter intake (DMI), and lactation performance of lactating dairy cows. Sixty-four multiparous, mid-lactation Holstein cows were enrolled in a 29-wk trial, and 32 cows were randomly selected for repeated MB. The MB and non-MB (NMB) cows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
4
3
0
1
Order By: Relevance
“…We found no effect of the mammary biopsy during the dry period on milk yield during the first 9 wk after calving (38.0 vs. 40.6 kg/d; SE = 3.4; P = 0.59). This is consistent with previous findings that mammary biopsies did not affect milk yield or composition in lactating cows (Weng et al, 2017).…”
Section: Short Communicationsupporting
confidence: 93%
See 4 more Smart Citations
“…We found no effect of the mammary biopsy during the dry period on milk yield during the first 9 wk after calving (38.0 vs. 40.6 kg/d; SE = 3.4; P = 0.59). This is consistent with previous findings that mammary biopsies did not affect milk yield or composition in lactating cows (Weng et al, 2017).…”
Section: Short Communicationsupporting
confidence: 93%
“…In the present study, cows were in heat stress conditions when pen temperature-humidity index was 77.6 (as described in greater detail by Fabris et al, 2017), although all enrolled cows received active cooling. Consistent with previous findings (Weng et al, 2017), we found no significant effect of mammary biopsy on DMI. Similarly, Mølgaard et al (2012) found no effect of liver biopsy on feed intake.…”
Section: Short Communicationsupporting
confidence: 92%
See 3 more Smart Citations